Chris Marker - Sixties - Marker, Chris; Marret, Mario; Reichenbach, François; L'Homme, Pierre; Bordès, Christian; Le Moal, Pascal; Millié, Robert (Arte Editions, 2013)
The Sixth Side of the Pentagon (1968): On October 21, 1967, over 100,000 protestors gathered in Washington, D.C., for the mobilization to end the war in Vietnam. It was the largest protest gathering yet, and it brought together a cross-section of liberals, radicals, hippies and Yippies. For many it was the transition from simply marching against the war, to taking direct action to stop the "American war machine." [www.dvdempire.com]
Keywords: DVD-Video